Multinationals offshore sourcing of finance and accounting in Malaysia: exploring the drivers from the perspectives of transaction costs, resource-based view and location advantages - Hoh, Jeannie Kwan Mun (2020)
The purpose of this research is to analyse the effects of drivers from the perspectives of Transactions costs economics (TCE), Resource-based view and Location Advantages on multinationals (MNCs) Finance and Accounting (FA) offshore sourcing strategy. A survey was developed to evaluate the significance of these drivers based on Malaysia-based MNCs with FA offshore establishments. Hypotheses are developed to advance the understanding of the effects of these drivers. Evidence from the study shows that uncertainty due to technology positively and significantly affects offshore insourcing of FA activities. Human asset specificity, which is always presented as inversely related to offshore outsourcing, demonstrated inconsistent effects. Apart from the economic factors, strategic value FA activities and the development of skills that are customised to the requirement of the firm affect offshore insourcing of FA. However, unique skills do not play any significant role. The study proposed the existence of a synergistic relationship between TCE and RBV. The interaction effects between uncertainty due to technology and strategic value FA activities on offshore insourcing strategy is evidenced, proving that this collaborated effort will not only empower the MNCs to create competitive advantage through innovating their FA processes, it also indicates using TCE and RBV in tandem elevates the benefits of offshore sourcing decision. Results show that the relationship between the integrated TCE and RBV drivers and offshore insourcing strategy is affected positively by the presence of location advantages. Results also revealed MNCs’ aspirations in offshoring FA activities deviate from solely seeking costs effectiveness or in acquiring FA professionals. The findings suggest the effectiveness of offshore insourcing of FA activities depends on the technological development of digital solutions along with the reengineering of specific capabilities and the access to location advantages such as innovations and technical competence. Analyses indicate this portfolio of factors expand MNCs’ FA sourcing footprint to the next level which is the offshore insourcing of highly strategic and complex FA processes.